Characterization of brick masonry: Study towards retrofitting URM walls with timber-panels - Dauda, Jamiu A. (2018)
The overall purpose of this study is to explore the possibility of using timber-panels to retrofit URM walls. However, this paper only present the overall proposed experimental program together with the experimental characterization of mechanical properties of masonry components: units and mortar. The present work developed finite element numerical model that is able to predict the strength of the masonry cube, on the safe side. The numerical model was validated with an experimental test on masonry cube showing 9% difference in the maximum compressive strength of masonry. The modelling technique adopted is the detailed micro modelling where the unit and mortar were represented by their respective mechanical properties using ABAQUS. Because, the numerical results compliment what was observed during the experimental test, then the developed model can be used to predict the general behaviour of masonry wall in the subsequent study.